Synthesis and Characterisation of Hydrated Calcium Pyrophosphate Phases of Biological Interest. Issue 34 (14th October 2013) - Gras, Pierre; Rey, Christian; Marsan, Olivier; Sarda, Stéphanie; Combes, Christèle
Abstract: The details of a synthesis method for biologically relevant hydrated calcium pyrophosphates (CPPs, Ca2 P2 O7 · n H2 O) has been elucidated. Control of the pH (from 3.6 to 5.8) and the temperature (from 25 to 90 °C) during the synthesis enabled the preparation of four pure CPP phases within one hour without intermediates: monoclinic and triclinic calcium pyrophosphate dihydrate (CPPD, Ca2 P2 O7 · 2H2 O), which are the two CPP phases detected in vivo in joints of arthritic patients, monoclinic tetrahydrate β (CPPT, Ca2 P2 O7 · 4H2 O) and an amorphous phase (a‐CPP, Ca2 P2 O7 · n H2 O). Four domains corresponding to the four different phases of hydrated calcium pyrophosphate were identified; a‐CPP was synthesised over a very wide pH and temperature range (up to 90 °C) within the domain of synthesis conditions explored, including physiological conditions (pH 7.4 and 37 °C). The as‐synthesised hydrated CPP phases were characterised by complementary techniques (powder X‐ray diffraction, FTIR and Raman spectroscopy, scanning electron microscopy and thermogravimetry) and chemical analyses. Rietveld refinement analyses of the as‐synthesised crystalline phases were performed, and there were significant differences between the m‐CPPD X‐ray diffraction pattern observed and previously published cell parameters. Vibrational spectroscopy allowed the crystalline and amorphous phases synthesised to be clearly distinguished and identified owing to the high flexibility of the pyrophosphate anion. Chemical analyses showed that the synthesis conditions used in this study did not allow significant hydrolysis of the pyrophosphate ions into phosphate ions, and the number of water molecules associated with each synthesised CPP phase was determined by thermogravimetric analysis. Different mechanisms of dehydration were also identified. The study of the formation of synthetic and well‐characterised hydrated calcium pyrophosphate phases and their availability in large amounts in vitro could allow progress to be made on the biological role of these phases and their possible transformations. This could also aid their detection in patients suffering from disease caused by calcium salt crystals and could clarify the mechanism by which CPP crystals form and evolve in vivo. Abstract : Four forms of calcium pyrophosphate hydrate (CPP) have been synthesised and characterised by complementary techniques. There are no intermediates or other metal ions in the fast one‐step synthesis method, which is performed under controlled pH and temperature. This approach may help us to understand the formation of CPP crystals, which are involved in several types of arthritis.